University-Wide Online Learning During COVID-19: From Policy to Practice - Tuaycharoen, Nuengwong (International Journal of Interactive Mobile Technologies (iJIM), 2021)
During Thailand’s COVID-19 lockdown, all university in the country must continue their classes in the Summer Semester with on-line format. This article described our university’s policy and practice to support university-wide on-line learning. Our support system included a Learning Management System, a teaching guideline for our instructors, an on-line training course for instructors, a quality control process, and a teaching assessment to obtain feedbacks from students. Due to the rushing nature of the situation, many instructors could not finish all teaching preparation before the semester started. However, the results showed that the students satisfied with their on-line classes with the average score of 4.54 from 5-point Likert Scale.